The Educational Role of Muslim Women During the Time of the Prophet Muhammad in the Development of Islamic Education - Sriwahyuni Lubis; Yusnaili Budianti; Azizah Hanum OK (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the social role of Muslim women during the time of the Prophet Muhammad (peace be upon him) in the context of the social changes that occurred following the advent of Islam. The background of this study is based on the pre-Islamic conditions of Arab women, who faced various limitations in many aspects of life and subsequently underwent significant transformation after the advent of Islamic teachings. The method used is a qualitative historical approach employing documentation techniques, analysis of classical and contemporary literature, and critical interpretation of primary sources such as the Qur’an, hadith, and the Prophet’s biography (sirah nabawiyah). The analysis is conducted descriptively to trace the dynamics of Muslim women’s social roles within their historical context. The research findings indicate that Muslim women during the time of the Prophet Muhammad (peace be upon him) made significant contributions in various fields, including education, da’wah, the economy, health, and humanitarian activities.